Experimental study of expanded cork agglomerate blocks – Compressive creep behavior and dynamic performance. (30th August 2018) - Dias, Sara; Tadeu, António; António, Julieta; Almeida, João; Pedro, Filipe; Martins, Saúl; Serra, Catarina
Highlights: Characterization of ICB when subjected to prolonged static and dynamic loads. ICB with low mass density can suffer large deformations under heavy loading. ICB specimens with lower mass density and larger thickness had better performance. Creep affects negatively the dynamic behavior in the initial stages of loading. ICB material is a more sustainable alternative to other commonly used products. Abstract: The main goal of the present work is to experimentally evaluate the behavior of expanded cork agglomerate blocks subjected to static and dynamic loads. The study focuses on the compressive and creep effects and on the vibration isolation capability. First, compressive creep behavior and deformation recovery capability (after loading) tests were performed on blocks made of expanded cork agglomerate. The dynamic characterization then involved performing transmissibility tests for different static and dynamic loading conditions and evaluating the dynamic transfer stiffness and damping ratio of the blocks. The resulting transmissibility curves indicate how much vibration is transmitted through the isolator to its base at a given frequency. These tests were also performed under different conditions of strain to better understand the effect on the dynamic performance of the material, and to assess whether it might be a limiting factor. The results show that expanded cork agglomerate blocks, especially those with higher mass density, have physical and mechanical properties that provide this material with great potential for withstanding heavy static loads since small compressive creep effects and low permanent deformation was exhibited. The results also indicate that expanded cork agglomerate can be a good option for mitigating vibration. It was found that specimens with lower mass density and larger thickness performed better, with higher vibration isolation and a wider range of frequencies isolated. However, this behavior is limited by the influence of compressive stress on the blocks.